2023
DOI: 10.3390/cancers15030934
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Validation of the ROL System in Substaging pT1 High-Grade Urothelial Carcinoma: Results from a Mono-Institutional Confirmatory Analysis in BCG Treated Patients

Abstract: Patients with pT1 high-grade (HG) urothelial carcinoma (UC) and a very high risk of progression might benefit from immediate radical cystectomy (RC), but this option remains controversial. Validation of a standardized method to evaluate the extent of lamina propria (LP) invasion (with recognized prognostic value) in transurethral resection (TURBT) specimens is still needed. The Rete Oncologica Lombarda (ROL) system showed a high predictive value for progression after TURBT in recent retrospective studies. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Our findings are in agreement with previous studies [24,25]. De Jong et al [24] recently reported on a cohort of 264 patients who received at least five out of six instillations of BCG induction course, demonstrating that extensive invasion of the LP (>0.5 mm or >1 focus) was associated with a higher risk of HG recurrence and progression.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are in agreement with previous studies [24,25]. De Jong et al [24] recently reported on a cohort of 264 patients who received at least five out of six instillations of BCG induction course, demonstrating that extensive invasion of the LP (>0.5 mm or >1 focus) was associated with a higher risk of HG recurrence and progression.…”
Section: Discussionsupporting
confidence: 93%
“…The ‘Rete Oncologica Lombarda’ (ROL) T1 substaging system was validated in a cohort of patients undergoing treatment with at least one induction course of BCG. Patients with a single focus of LP invasion extending >1.0 mm or multiple foci of LP invasion extending >1.0 mm summed together (ROL 2) showed, in adjusted multivariable regression analysis, a more than twofold risk of progression to MIBC (hazard ratio 2.88; P = 0.01) compared to those with LP invasion <1 mm (ROL 1) [25]. T1 substaging remains underutilised and not routinely reported in pathology reports.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the validity of the ROL sub-staging system for oncological outcomes was recently evaluated and the system reliably stratified patients, with ROL 2 having lower PFS and RFS. 29 Further studies will help consolidate the oncological impact of this innovative staging system. A critical issue with T1 sub-staging systems is their feasibility, which is not the same among different systems.…”
Section: Discussionmentioning
confidence: 99%